Sizing, selection, and comparison of heat exchangers considering the lowest saving-investment ratio corresponding to the area at the tag end of the heat exchanger - Teke, Ismail; Agra, Ozden; Demir, Hakan; Atayilmaz, S. Ozgur (PERGAMON-ELSEVIER SCIENCE LTD, 2014)
A new method has been developed to determine the area of waste heat recovery heat exchangers considering the lowest saving-investment ratio corresponding to the area at the tag end of the heat exchanger. Applying this method to any existing heat exchanger, the saving-investment ratio performance considering the area at the tag end of the heat exchanger can also be determined and compared with its optimum value having the same technical and economical parameters. In this study, the distributions of saving-investment ratio in heat exchangers have been obtained based on known technical and economical parameters and NTU (Number of Transfer Units) as d(TYO) = E/E-opt, where E-opt is investment saving potential ratio at optimum, E is local investment-saving potential ratio and dimensionless, which is suggested as Teke Number and it is derivatives of effectiveness according to NTU. E functions are obtained and represented on epsilon-NTU charts for all type of heat exchangers. Based on these charts, heat exchanger area can be determined for a given E value corresponding to the area at the tag end of the heat exchanger. By comparing the epsilon or NTU values of different type heat exchangers having the same E values, the best one is chosen. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Effectiveness; NTU; Heat exchangers; Economical; Optimization; DESIGN; Thermodynamics; Energy & Fuels